Law and the Transition to Business Sustainability - Cahoy, Daniel R.; Colburn, Jamison E.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book examines the key legal and business aspects of sustainability in depth. Recognizing the firm's need for integrated approaches to law and sustainability as well as adaptive goal setting, the book unites scholars from environmental law, energy, risk regulation and intellectual property.  Most firms now recognize that global resources are finite and will grow increasingly scarce. They acknowledge that their actions have social, economic and environmental consequences.  Some firms now practice "whole life-cycle" analysis in marketing and product design, seek sustainable inputs and energy sources, and track and report sustainability performance overall, however it can be measured. But standard practices have not kept pace. Regulators must support such efforts with mandatory structures for all firms enabling leaders to gain competitive advantages and laggards to pay the price. The variety of regulatory tools has grown to include cooperative funding, intellectual property rights, information disclosures, and other means. And that variety is most urgently needed in transition economies where the forces of international competition can be the strongest. The chapters in this book push beyond the traditional boundaries separating these dimensions of law, business and sustainability to offer both practical insights and directions for future research in this immense and growing nexus.
Design for Regulation: Integrating Sustainable Production into Mainstream Regulation -- Mandating Sustainability: When Federal Legislation May Preempt the Best Green Building Code Intentions -- An Operational Look at Take-Back Legislation -- Subsidizing Sustainability: The Role of the State and Civil Society in Implementing Wal-Mart's Local Produce Sourcing Program -- IPRs and the Transfer of Technologies that Combat Climate Change: the Untapped Potential of Licensing -- The Benefits of a Sustainable Energy Trade Agreement (SETA) -- The Future of Sustainability Reporting as a Regulatory Mechanism -- Green washing 2.0: Identifying a New Paradigm Through B-to-B Threat Matrices.
Keywords: International law; Trade; Environmental law; Environmental policy; Sustainable development; Law and economics; Economics; Law and Economics; International Economic Law, Trade Law; Environmental Law/Policy/Ecojustice.; Sustainable Development